Ação controlada nos crimes de natureza econômica - Santos, André Luiz Nogueira dos (2023)
The Brazilian State has been engaged in dismantling and dismantling organized criminal organizations, which has allowed them to develop and improve effective methods. Brazil's battle against criminal organizations is based on investigation and repression techniques established by law and which were based on existing methods and formed in comparative law in order to be used against different types of organized crime. When researching the most important law enforcement tools available to law enforcement, it is common to find mentions of electronic surveillance, undercover operations, undercover agents, eavesdropping, and more. The use of tools such as the infiltration of agents, the use of eavesdropping, etc., belong to what is called Controlled Action in Brazilian legislation. Introduced by Law 12.850/2013, controlled action is a criminal investigative technique, used as a means of obtaining evidence for criminal proceedings. When well used, it constitutes a valuable and indisputable means of investigation to combat criminal organizations that put the economic interests of the state and its citizens at risk and in danger. For the development of this study, this research has the general objective of presenting the investigative and evidence collection method called Controlled Action to combat organized crime in the Brazilian economic criminal sphere. For this purpose, the bibliographic review method was used, which has books, articles, theses, dissertations, laws and other academic content relevant to the approach in question as a source of research. It is concluded that the Controlled Action presents itself as an efficient tool for obtaining evidence, as long as the law and the limits imposed on this modality are observed, having a high efficiency index according to the cases presented. Finally, this study does not exhaust the subject in question, therefore, it is suggested that a new study be carried out in the future, for jurisprudential analysis and specific cases where Controlled Action was used, in order to understand the investigative methods used and the its developments.